Four groups of noncommunicable diseases in outpatient health care: analysis of medical information system data - Ekaterina P. Kakorina; Irina V. Samorodskaya; Vera N. Larina; Vladimir G. Larin (КардиоСоматика)
BACKGROUND: The World Health Organization uses the concept of four major groups of noncommunicable diseases, which are associated with high mortality rates, to inform prevention and mortality reduction strategies.